Helmintos parásitos de peces de la familia Lepisosteidae de aguas dulces de México. I. Trematoda - Caballero y C., Eduardo (1974)
A new genus Neotropicotrema, with the type species N. bychowskyi, is described. The new genus is characterized by having a large, bell-shaped oral sucker, a short prepharynx, a rather muscular pharynx, a short esophagus, and two intestinal caeca that fuse posteriorly to form an arch. The cirrus sac is well developed, partially surrounding the acetabulum; the seminal vesicle is formed by two distinct parts; the genital pore is located between the intestinal fork and the anterior margin of the acetabulum. The testes are caudal, large and next to the intestinal arch. The yolk glands are located laterally, forming bands. The excretory pore is terminal, and communicates with a Y-shaped vesicle that does not extend beyond the lower half of the body.